2017
DOI: 10.1177/2333393617713097
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Diabetes Self-Management Among Medically Underserved Patients With Type II Diabetes

Abstract: In this study, researchers compare and contrast issues regarding diabetes self-management between persons in good versus poor glycemic control. The sample comprises low-income racially diverse adults with diabetes from four mid-western community health centers; 44 patients participated in eight focus groups divided by control status (HbA1c of > 9 [uncontrolled] or < 7 [controlled]). Themes common to both groups included the impact of dietary restrictions on social interactions, food cravings, the impact of men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 57 publications
(80 reference statements)
5
59
0
1
Order By: Relevance
“…In contrast, relationships with friends and other non‐family members may prevent adoption of a healthy diet. More specifically, a study of patients with diabetes reported that dietary alterations were perceived to interfere with social interactions, and patients often avoided gathering with friends because it led to consumption of unhealthy foods (Reyes, Tripp‐Reimer, Parker, Muller, & Laroche, ). In agreement, we found that support from family rather than friends was more useful for development of self‐leadership for adopting a healthy diet.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, relationships with friends and other non‐family members may prevent adoption of a healthy diet. More specifically, a study of patients with diabetes reported that dietary alterations were perceived to interfere with social interactions, and patients often avoided gathering with friends because it led to consumption of unhealthy foods (Reyes, Tripp‐Reimer, Parker, Muller, & Laroche, ). In agreement, we found that support from family rather than friends was more useful for development of self‐leadership for adopting a healthy diet.…”
Section: Discussionmentioning
confidence: 99%
“…37 Barriers to appropriate self-care observed in our study have been reported in previous studies around the world. [38][39][40][41][42][43] Dietary adherence was impeded by the cost of healthful foods and personal factors such as taste and inability to resist temptations and hunger. The social environment and lack of family support were also mentioned to negatively affect dietary adherence, similar to other studies, 9,[40][41][42][43]44 even in the primary care setting 36 Unlike their primary care setting counterparts, patients in this study did not raise physical access to healthful foods as an issue.…”
Section: Discussionmentioning
confidence: 99%
“…The American Diabetes Association has suggested that diabetes mellitus self-management (DMSM) practice is greatly influenced by the level of patients' own participation in care [7]. Some studies also confirmed that DMSM practice could improve patients' perceived obstacles to behavioral adherence [8,9], which is essential to achieving optimal glycemic control and medication adjustment in the context of daily living [10]. However, it is a challenge to perform DMSM for the persistent control of blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%